2013
DOI: 10.1111/jonm.12141
|View full text |Cite
|
Sign up to set email alerts
|

The (mis)management of migrant nurses in the UK: a sociological study

Abstract: We offer a management strategy to bring policies for the migrant workforce into line with the wider workforce plans by supporting nurses in finding jobs relevant to their expertise and providing career pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
76
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(78 citation statements)
references
References 9 publications
0
76
0
2
Order By: Relevance
“…The excluded studies that were read in full did not report data on working conditions or health-related outcomes in a defined working population ( n = 53); three were duplicates, and two were historical studies of asbestos and mesothelioma [ 92 , 93 ]. Twenty-one studies [ 94 114 ] did not report relevant quantitative measures of exposure or health. Thus, 82 studies were included in this review (see the flow chart in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The excluded studies that were read in full did not report data on working conditions or health-related outcomes in a defined working population ( n = 53); three were duplicates, and two were historical studies of asbestos and mesothelioma [ 92 , 93 ]. Twenty-one studies [ 94 114 ] did not report relevant quantitative measures of exposure or health. Thus, 82 studies were included in this review (see the flow chart in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The UK health system had major pull factors for both nurses and doctors for career advancement [ 22 – 29 ], training [ 22 , 23 , 26 , 27 , 30 , 31 ], safety and security of the NHS [ 22 – 24 , 26 , 27 , 30 , 31 ] and economic benefits [ 23 26 , 29 35 ]. This was promoted by active recruitment, relocation packages for nurses and doctors from the EU [ 22 , 30 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The push factors of source country were corruption [ 24 , 25 , 34 ], poor health infrastructure [ 25 , 30 ] and lack of career advancement and training [ 27 , 30 , 35 ]. Access to the internet in the source countries facilitated nurses’ migration, by providing insight into wider nursing practices and online application to registration and employment in the UK [ 23 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…A study of Asian nurses in Australia found that although most of the participants were satisfied with their working conditions, deficits in the majority language coupled with differences in culture could create misunderstandings (Takeno, ). Studies from multicultural nursing homes point to discrimination by residents, managers or colleagues (Dahle & Seeberg, ; Huang, Yeoh, & Toyota, ; Näre, ; Timonen & Doyle, ), while others identify deskilling (Adhikari & Melia, ; Iredale, ; Likupe, ; Riemsdijk, ; Seeberg, ). Deskilling in this context is defined as the undervaluing of immigrants’ skills, education and experience, which results in various workplace disadvantages (Creese & Wiebe, , p. 58).…”
Section: Introductionmentioning
confidence: 99%